Toxicity of Beauty Salon Effluents Contaminated with Hair Dye on Aquatic Organisms - Gonçalves, Letícia C. [UNESP]; Roberto, Matheus M.; Peixoto, Paloma V. L. [UNESP]; Viriato, Cristina [UNESP]; da Silva, Adriana F. C. [UNESP]; de Oliveira, Valdenilson J. A. [UNESP]; Nardi, Mariza C. C.; Pereira, Lilian C. [UNESP]; de Angelis, Dejanira de F. [UNESP]; Marin-Morales, Maria A. [UNESP] (MDPI, 2023)
Cosmetic residues have been found in water resources, especially trace elements of precursors, couplers, and pigments of hair dyes, which are indiscriminately disposed of in the sewage system. These contaminants are persistent, bioactive, and bioaccumulative, and may pose risks to living beings. Thus, the present study assessed the ecotoxicity of two types of effluents generated in beauty salons after the hair dyeing process. The toxicity of effluent derived from capillary washing with water, shampoo, and conditioner (complete effluent—CE) and effluent not associated with these products (dye effluent—DE) was evaluated by tests carried out with the aquatic organisms Artemia salina, Daphnia similis, and Danio rerio. The bioindicators were exposed to pure samples and different dilutions of both effluents. The results showed toxicity in D. similis (CE50 of 3.43% and 0.54% for CE and DE, respectively); A. salina (LC50 8.327% and 3.874% for CE and DE, respectively); and D. rerio (LC50 of 4.25–4.59% and 7.33–8.18% for CE and DE, respectively). Given these results, we can infer that hair dyes, even at low concentrations, have a high toxic potential for aquatic biota, as they induced deleterious effects in all tested bioindicators.
Keywords: aquatic ecotoxicology; cosmetic residues; ecotoxicity; emerging environmental contaminants; lethality test; zebrafish embryotoxicity